Decomposition kinetics of uronic acids obtained from kelp under hydrothermal condition. Issue 2 (April 2017) - Mohamad, Rozyanti; Aki, Tsunehiro; Nakashimada, Yutaka; Okamura, Yoshiko; Tajima, Takahisa; Matsumura, Yukihiko
Abstract: The main objective of this study was to obtain guidelines for the hydrothermal pretreatment of kelp for the isolation of uronic acids. This was done by determining the effect of hydrothermal treatment on the kinetic of the decomposition of mannuronic acid (MA) and guluronic acid (GA). These uronic acids were obtained by the hydrolysis of alginic acid originating from kelp. Each uronic acid was treated under hydrothermal conditions using a continuous-flow reactor. The temperature ranged from 170 to 250 °C, the residence time was varied between 5 and 100 s, and the pressure was set at 25 MPa. The decomposed products were analyzed with high-performance liquid chromatography (HPLC). The yields of both uronic acids showed similar trends; they decreased as the temperature was increased. Activation energies for the decomposition of MA and GA were approximately 28.3 and 20.6 kJ/mol, respectively, and pre-exponential factors were determined to be 282 and 40.6 s −1, respectively. Uronic acids were readily decomposed under hydrothermal conditions. Calculations showed the superiority of the continuous reactor over the autoclave reactor, in terms of the recovery of uronic acids. Highlights: Individual behavior of GA and MA was determined under hydrothermal condition using continuous flow reactor. Decomposition characteristic of GA and MA was explained based on the effect of reaction temperature and residence time. Reaction parameters were calculated to clearly elucidate the kinetics behavior of GA and MA.